FILOSOFI EPISTEMOLOGI STIMULASI EMOSIONAL TERHADAP KECEMBURUAN SOSIAL ANAK USIA DINI - Dtakiyyatuddaaimah; Irna; Yunica, Winda; Wulandari, Widiya Apriliani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the application of emotional stimulation based on philosophical and epistemological approaches in overcoming social jealousy in early childhood. The background of this study stems from the phenomenon of social jealousy that often arises in children aged 4–5 years, especially in early childhood education settings, which has the potential to hinder their social-emotional development. The study was conducted at Aisyiyah 01 Leuwiliang Kindergarten using a qualitative case study approach. The research subjects included the school principal, classroom teachers, parents, and children in Group A. Data collection techniques were conducted through observation, interviews, and documentation, with validation using source and technique triangulation. The study revealed that the strategies employed to stimulate emotions included fostering good behavior, group games that build empathy, simple discussions about feelings, and direct teacher intervention in resolving conflicts. The implementation of these strategies was consistent and supported by collaboration between the school and parents. The results of the study indicate a significant decrease in social jealousy behavior, an increase in the ability to wait for one's turn, and an increase in children's empathy toward peers. Emotional stimulation based on philosophical and epistemological approaches has proven effective in reducing social jealousy and creating a harmonious, empathetic, and inclusive learning environment. This is the conclusion of this study. It is recommended to integrate these strategies into early childhood education as a preventive and curative measure in the social-emotional development of children